dari Pelecehan Menjadi Stigma: Normalisasi Kekerasan Patriarki dalam 'Women from Rote Island' - Dwi Oktarina; Eni Murdianti; Muslimin (ALAMTARA, 2025)
This study explores the representation of patriarchy in the film Women from Rote Island using a qualitative approach with Roland Barthes’s semiotic analysis. This approach was chosen because it enables the researcher to uncover symbolic meanings, cultural values, and gender ideologies embedded in the audiovisual text. Primary data consist of the film itself, analyzed through elements such as dialogue, gestures, facial expressions, costumes, setting, props, cinematography, and narrative plot. Secondary data include books, journal articles, film reviews, and literature on semiotics, gender, and media. Data were collected through documentary observation (repeated screenings, transcription of key dialogues, and relevant screenshots) and literature review. Analysis followed Barthes’s three stages: denotation, connotation, and myth. The findings reveal that patriarchy operates through harassment, objectification, stigma, and social neglect, which normalize violence and shift blame onto women (victim blaming). The film articulates moral imperatives such as: ending victim blaming, reinterpreting customary law as protection of dignity, fostering empathetic masculinities, ensuring safe public spaces, dismantling stigma as a silencing tool, and demanding state and law enforcement support for survivors. Thus, Women from Rote Island not only exposes the wounds of patriarchy but also conveys an ethical call for protection and the construction of a just and gender-equal culture.